2022
DOI: 10.1002/cb.2022
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social commerce on eco‐friendly consumer behavior: Technological and social roles

Abstract: There is much evidence that consumers' eco-friendly consumption behaviors have changed with the development of the mobile internet economy and social networks.Social commerce, which combines social media and e-commerce, is widely used to promote eco-friendly consumption behavior. However, there has been insufficient empirical research into how technological and social factors affect consumers' ecofriendly behavior in the social commerce context. Taking the "Green Box Area" program based on Alibaba Group's two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 111 publications
0
18
0
Order By: Relevance
“…Verplanken suggests that "behaviour is strongly influenced by other people, either by what they do or by what we think they want us to do, that is, by 'social norms '" (2017, p. 196). Gao et al (2022) demonstrated in their studies how social factors and technology could mobilise consumers towards eco-friendly consumption habits. As a result, it appears that changing the habits of consumers is most successful in doing so in a personal way or by technology.…”
Section: Habits and Behavioursmentioning
confidence: 99%
“…Verplanken suggests that "behaviour is strongly influenced by other people, either by what they do or by what we think they want us to do, that is, by 'social norms '" (2017, p. 196). Gao et al (2022) demonstrated in their studies how social factors and technology could mobilise consumers towards eco-friendly consumption habits. As a result, it appears that changing the habits of consumers is most successful in doing so in a personal way or by technology.…”
Section: Habits and Behavioursmentioning
confidence: 99%
“…Third, social factors are one of the important antecedents influencing green consumption behavior (Choudhary et al, 2019; Gao et al, 2022; Wang et al, 2019), such as social influence and social norms. When friends and colleagues buy green products or participate in green‐related activities, individuals tend to follow their behaviors (Lazaric et al, 2019; Salazar et al, 2013; Wang et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Visualized, this represents a row of rubbish vehicles over 3,100 miles long each day (World Bank, 2013). As such, academic researchers and green consumers need to join the conversation about what constitutes eco-friendly behavior (ECB) and what factors trigger their buying preferences (Gao et al, 2022;Kim et al, 2019).…”
Section: / 15mentioning
confidence: 99%